EFEK MOTIVASI KARIR DAN KEPUASAN KARIR PADA PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KEPUASAN KERJA PADA BANK SYARIAH “X” DI JAKARTA - Sylvia Diana Purba (Jurnal Manajemen, 2013)
This research aims to identify and examined howthe transformational leadership influenced the job satisfaction with career motivation and career satisfaction asmoderating and intervening variables. Data were collected from 51 Syariah Bank “X” employeesin Jakarta. The result showed that career satisfaction can not be an intervening variable on the effect of transformational leadership toward job satisfaction. In the other side the career motivation have significant impact as a moderating variable when the transformational leadership is raising the job satisfaction.